Construction of the in-between identity in Kate Chopin's The Awakening and Sylvia Plath's Bell Jar - Hosseinifar, Seyedeh Maryam (2012)
In both Kate Chopin’s The Awakening and Sylvia Plath’s The Bell Jar, one encounters a significant problem regarding the female characters’ responses to patriarchal rules and regulations of the symbolic order. The heroines of both these novels, upon reaching a critical point in their lives begin to display a tremendous dissatisfaction toward their predetermined and prescribed gender roles imposed on them via symbolic order’s systems of rules and values. Therefore, they start distancing themselves from their prescribed identity in favor of a new fluid identity which allows them to resist against these adamant and deep-seated roles. For this very reason, this thesis aims to examine the complexity of the process of subjectivity of the heroines of these novels; namely, Edna and Esther, in the light of Kristeva’s psychoanalytical theoretical framework regarding the formation of the female subject, to unravel the motives which may have motivated them to rewrite their identities. As a response, it is argued that by maintaining an “in-between identity” the heroines of these novels awaken their repressed semiotic desires in the symbolic order in order to elude the restrictiveness of the patriarchal logic and accordingly rewrite their phallic identity.